Modeling the performance of hazardous wastes removal in bioaugmented activated sludge processes - Leu, Shao-Yuan (Water environment research : a research publication of the Water Environment Federation, 2009)
An enricher-reactor process in which acclimated biomass is grown in an offline reactor on high concentrations of enrichment substrates was used to bioaugment a conventional activated sludge process to a toxic compound, 1-amino naphthalene. Various levels of bioaugmentation, ranging from 1 to 16% mass ratio of augmented cells to indigenous cells, were evaluated in laboratory-scale reactors. The experimental results showed that bioaugmentation can enhance toxic compound removal, increase resistance to shock loading, and reduce the time required for acclimation to the toxic compound. A process model was developed and calibrated using the experimental data. This model was then used to compare the process to an in-situ bioaugmentation process using a reaeration reactor that receives a portion of the recycle activated sludge. The model predicted experimentally observed removals of toxic compound and decreasing relative benefits of bioaugmentation at higher levels. The model suggests that augmented biomass suffers higher decay, which likely is due to the effects of its removal from a substrate-rich to substrate-poor environment. The model shows that the enricher-reactor-process has advantages at lower mean cell retention time (MCRT), and the in-situ process is superior at higher MCRT. Both processes can remove the toxic compound when operating below the washout MCRT that would occur in an unaugmented activated sludge process